2016
DOI: 10.1038/srep33367
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding reveal patterns of species diversity among northwestern Pacific molluscs

Abstract: This study represents the first comprehensive molecular assessment of northwestern Pacific molluscs. In total, 2801 DNA barcodes belonging to 569 species from China, Japan and Korea were analyzed. An overlap between intra- and interspecific genetic distances was present in 71 species. We tested the efficacy of this library by simulating a sequence-based specimen identification scenario using Best Match (BM), Best Close Match (BCM) and All Species Barcode (ASB) criteria with three threshold values. BM approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…Thus, for species complexes where maximum intraspecific distance exceeds the distance to the nearest neighbor, species-level identification becomes ambiguous (Jinbo, Kato, & Ito, 2011;Sun et al, 2016). The accuracy of DNA metabarcoding identification depends on the "barcode gap," the existence of a gap between interspecific and intraspecific genetic divergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for species complexes where maximum intraspecific distance exceeds the distance to the nearest neighbor, species-level identification becomes ambiguous (Jinbo, Kato, & Ito, 2011;Sun et al, 2016). The accuracy of DNA metabarcoding identification depends on the "barcode gap," the existence of a gap between interspecific and intraspecific genetic divergence.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of DNA metabarcoding identification depends on the "barcode gap," the existence of a gap between interspecific and intraspecific genetic divergence. Thus, for species complexes where maximum intraspecific distance exceeds the distance to the nearest neighbor, species-level identification becomes ambiguous (Jinbo, Kato, & Ito, 2011;Sun et al, 2016). There are various reasons resulting in the lack of large interspecific divergence, such as hybridization between closely related species, short time since speciation, and incomplete lineage sorting (Lin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The COI gene is recommended as the standard barcoding marker for most animals (Renxie et al, 2018). Based on COI barcoding, high rates of species-level identification are well documented in many animal species, for instance, 95.27% for numerous northwestern pacific mollusks (Sun et al, 2016) and 98% for marine fishes (Ward, 2009). In addition, many studies have shown that intraspecific variation of COI barcodes is generally pretty small and clearly discriminable from interspecific variation (Hubert et al, 2008;Steinke et al, 2009;Ward et al, 2009;Bucklin et al, 2011).…”
Section: Molecular Analysismentioning
confidence: 99%
“…The neotropical skipper butterfly Astraptes fulgerator is the best example (Hebert et al, ). Other animals, such as the bumble bee (Scriven, Whitehorn, Goulson, & Tinsley, ), mollusk (Sun et al, ), frog (Stuart, Inger, & Voris, ), and fish (Borsa, Hsiao, Carpenter, & Chen, ; Feulner, Kirschbaum, Schugardt, Ketmaier, & Tiedemann, ; Rosser, ), were also revealed to contain sympatric cryptic species as detected through mtDNA sequence analysis. The COI sequence is usually used as DNA barcoding for species identification with the criterion of 2% or 3% sequence divergence (e.g., Costa et al, ; Hebert et al, ; Loh, Bond, Ashton, Roberts, & Tibbetts, ; Shen, Guan, Wang, & Gan, ; Ward et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other animals, such as the bumble bee (Scriven, Whitehorn, Goulson, & Tinsley, 2016), mollusk (Sun et al, 2016), frog (Stuart, Inger, & Voris, 2006), and fish (Borsa, Hsiao, Carpenter, & Chen, 2013;Feulner, Kirschbaum, Schugardt, Ketmaier, & Tiedemann, 2006;Rosser, 2015),…”
Section: Sympatric Population and Evolutionary Originally Hypothesismentioning
confidence: 99%